Des Miracula inédits de Saint Géraud d'Aurillac († 909) Étude, édition critique et traduction française - Bultot-Verleysen, Anne-Marie (Analecta Bollandiana, 2000)
Critical edition and French translation of a collection of posthumous miracles of Saint Gerald of Aurillac (not in BHL), which also includes two chapters of a Liber Vite of the saint written after the Vita prolixior of Odo of Cluny (BHL 3411). These Miracula, which describe the conflicts of the abbey of Aurillac with lay lords at the end of the 11th century, is of undoubted historical interest. They are followed by a later short Continuatio of one of the miracles.